MEDICAL AND SOCIAL PROFILE OF WOMEN BEFORE TERMINATION OF PREGNANCY AT AN EARLY STAGE - Светлана Ивановна Елгина; Ольга Сергеевна Золотаревская; Виктория Анатольевна Разумова; Алексей Юрьевич Кратовский (The Publishing House Medicine and Enlightenment, 2018)
Objective - to determine the medical and social profile of women before termination of pregnancy at an early stage. Materials and methods. 299 women of reproductive age who attended the female consulting centre of Clinical polyclinic N 20 in 2016 to have pregnancy terminated before 12 weeks of gestation. Results. It was found out that women aged 25-35, married, employed, who had deliveries and abortions in the past and rarely use contraceptives more often attend the centrefor abortion at an early stage of gestation. The main reasons to have pregnancy terminated were: poor financial situation, lack of housing, an unwanted pregnancy. Conclusion. Our study identified the medical and social profile of women before termination of pregnancy at the early stages. It showed not only economic but medical problem of abortion in the first place, use of contraceptives among women of reproductive age.